2010
DOI: 10.1016/j.concog.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Feeling of doing in obsessive–compulsive checking

Abstract: a b s t r a c tResearch on self-agency emphasizes the importance of a comparing mechanism, which scans for a match between anticipated and actual outcomes, in the subjective experience of doing.This study explored the ''feeling of doing" in individuals with checking symptoms by examining the mechanism involved in the experienced agency for outcomes that matched expectations. This mechanism was explored using a task in which the subliminal priming of potential action-effects (emulating outcome anticipation) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Consistently, the results of two studies [50,57] that investigated the sense of control in persons with OCD symptoms can be interpreted along the same lines. Participants with OCD symptoms (regardless of OCD subtype) may be characterized by an increased illusory sense of control in compulsive-like situations (i.e., when their actions are directed towards effortful attempts to control an event [50]).…”
Section: Summary and Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Consistently, the results of two studies [50,57] that investigated the sense of control in persons with OCD symptoms can be interpreted along the same lines. Participants with OCD symptoms (regardless of OCD subtype) may be characterized by an increased illusory sense of control in compulsive-like situations (i.e., when their actions are directed towards effortful attempts to control an event [50]).…”
Section: Summary and Discussionsupporting
confidence: 70%
“…Participants with OCD symptoms (regardless of OCD subtype) may be characterized by an increased illusory sense of control in compulsive-like situations (i.e., when their actions are directed towards effortful attempts to control an event [50]). However, only individuals with checking proneness appeared to experience an undermined sense of control in routine-like situations (i.e., when their actions are supposed to be automatically controlled, rather than under conscious monitoring [57]). This latter result is consistent with the van der Weiden et al [63] study in which people with a low level of agency were also found to be less prone to experience the illusion in the Wheel of Fortune task.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activity episodes in this data set tend to relate to OCD subtypes in the literature that have overt compulsions, such as checking to prevent danger and mistakes (e.g. Belayachi & Van der Linden, 2010), symmetry (e.g. Rasmussen & Eisen, 1992) and feelings of 'having to' perform an action until it 'feels right' without perceiving any benefit in performing that particular action (Coles, Frost, Heimberg, & Rheaume, 2003).…”
Section: Internally-directed Interactionmentioning
confidence: 99%